Purkinje cells and autism spectrum disorder. Is there an aetiological connection? - Lucci, Kamil D. (Neuropsychiatria i Neuropsychologia/Neuropsychiatry and Neuropsychology, 2018)
Autism spectrum disorder (ASD) is a neurodegenerative disorder affecting the quality of life of a significant number of children and adults around the world. Despite its growing epidemiology, the causes of autism are still not known. Research has linked the disorder with brain pathology, with a possible prenatal onset. It has been reported that the brain area involved in autism is the cerebellum, and more specifically, a disruption within Purkinje cells. For this reason, Purkinje cells are among the most studied brain cells in relation to ASD. Despite the amount of research on the topic and different techniques applied, the aetiology of ASD is still unclear. One of the possible causes of the relationship between ASD and Purkinje cell abnormality might be their vulnerability. Studies suggest that Purkinje cell loss might occur early in life (in the prenatal or neonatal period) as a result of contact with toxins or brain damage. The aim of this review is to describe the most important findings in the field and discuss the aetiological connection between Purkinje cell loss and ASD. First, this review discusses the neurological basis of autism. Then, the evidence of the link between Purkinje cell damage and ASD, presented in such studies, is described. The main part of the article analyses major studies within the field. They have been grouped based on the research techniques applied: mutant mice models, histopathological examinations, and in vivo neuroimaging. At the end, the limitations of the study and future research possibilities are discussed.